Implementasi Kebijakan Disiplin Pegawai Negeri Sipil di Sekretariat DPRD Provinsi Sulawesi Utara - Sultan, Iin Inriani; Rompas, Sonny; Dengo, Salmin (Sam Ratulangi University, 2015)
ABSTRACTTo realize the discipline of civil servants UU.NO.43 1999 mandates the need enactment ofgovernment regulations regarding the discipline of civil servants. In connection with it will emergeGovernment Regulation No. 53 of 2010 on Discipline of Civil Servants civil service discipline. This studyis intended to engetahui bagamana Impementasi the policy in Parliament Secretariat North Sulawesi, andthe extent of the impact of the implementation of that policy to increase employee discipline.This study uses research kualtatif.informan taken from elements of leadership and the elements of staff /executive secretariat in the northern Sulawesi Provincial Parliament, entirely as many as 15 peopleinformer. Insrumen in this study is the researchers themselves, while collecting data using techniques ofdata wawancara.analisis dilaukan with anaisis techniques Qualitative interactive model of Miles andHumbernann.research results conclusions: (1) Implementation of policy discipline PNS (PP.53 in 2010) has beendone with good views of pnting dimension of public policy implementation model of Edward III, kususnyacommunication factor (socialization) policies, and disiposisi (koitmen and consistency ) implementing thepolicy. In concrete policy implementation PNS discipline shown by some reality; socialization rules ofdiscipline, commitment and leadership to menerepkan mengakan disciplinary regulations, adnya efforts toraise awareness of employees to implement the provisions of the discipline as well as creating a culture ofdiscipline, and the enforcement of disciplinary punishment consistently; (2) Implementation of policydiscipline has given a positive dampa to increased discipline seen from increased adherence and provisionof personnel to the provisions concerning the obligations and prohibitions applicable to civil servants Yngsebagaiman stipulated in the PP. 53 out of 2010.Based on the conclusion of the study put forward suggestions: (1) the implementation of civilservice discipline policy should be more emphasis on the progressive increase in awareness that willmanifest pure discipline; (2) the employee should be encouraged to have a high commitment andconsistency in applying the rules of discipline of civil servants.Keywords: Policy Implementation, PNS Discipline Policy